2012
DOI: 10.2478/s11534-011-0123-3
|View full text |Cite
|
Sign up to set email alerts
|

Nonextensive statistical effects in the quark-gluon plasma formation at relativistic heavy-ion collisions energies

Abstract: Abstract:We investigate the relativistic equation of state of hadronic matter and quark-gluon plasma at finite temperature and baryon density in the framework of the non-extensive statistical mechanics, characterized by power-law quantum distributions. We impose the Gibbs conditions on the global conservation of baryon number, electric charge and strangeness number. For the hadronic phase, we study an extended relativistic mean-field theoretical model with the inclusion of strange particles (hyperons and meson… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 61 publications
1
34
0
Order By: Relevance
“…It may be stressed here that the results of this investigation should be useful for understanding the nonextensive effects in interstellar and space plasmas, 51,52 particularly in stellar polytropes, 14 hadronic matter, and quark-gluon plasma, 15 dark-matter halos, 53 etc., as well as laboratory plasmas. In conclusion, it may be proposed to perform a laboratory experiment which will be able to identify the special new features of the DIASWs propagating in a nonextensive four-component dusty multi-ion plasma.…”
Section: -4mentioning
confidence: 89%
See 2 more Smart Citations
“…It may be stressed here that the results of this investigation should be useful for understanding the nonextensive effects in interstellar and space plasmas, 51,52 particularly in stellar polytropes, 14 hadronic matter, and quark-gluon plasma, 15 dark-matter halos, 53 etc., as well as laboratory plasmas. In conclusion, it may be proposed to perform a laboratory experiment which will be able to identify the special new features of the DIASWs propagating in a nonextensive four-component dusty multi-ion plasma.…”
Section: -4mentioning
confidence: 89%
“…From the third order calculation, where another set of stretched coordinates is used, a mK-dV equation is obtained to explain the nonlinear evolution near the critical value. The mK-dV equation has been introduced by the stretched coordinates n ¼ ðx À V p tÞ; (15) s ¼ 3 t:…”
Section: Derivation Of Mk-dv Equationmentioning
confidence: 99%
See 1 more Smart Citation
“…Lima et al 45 confirmed experimentally the existence of non-Maxwellian velocity distribution and stated that the q-nonextensive formalism is very important for systems having long-range interactions those occurred in astrophysical environments. The new nonextensive theory provides a convenient frame for the analysis of a large number of astrophysical and cosmological systems and processes (e.g., stellar polytropes, 48 the solar neutrino studies, 49 velocity distributions of galaxies, 50 self gravitative systems, 51 quarkgluon plasma, 52 hadronic matter, dark matter halos, 53 and protoneutron stars 54 ). Liu and Goree 55 detected experimentally anomalous diffusion and non-Gaussian statistics fitting a Tsallis distribution in a two-dimensional driven-dissipative system.…”
mentioning
confidence: 99%
“…It has received a great deal of attention [28] due to its wide relevance in astrophysical and cosmological scenarios like stellar polytropes [30], hadronic matter and quark-gluon plasmas [31], protoneutron stars [32], dark-matter halos [33], etc. Nonextensive plasmas associated with ionacoustic waves, electron-acoustic waves, dust-ion acoustic (DIA) waves or dust-acoustic (DA) waves are investigated either by taking the electron to be nonextensive [34][35][36][37][38][39][40][41][42][43][44] or ion to be nonextensive [45] or by taking both the electron and the ion to be nonextensive [46].…”
Section: Introductionmentioning
confidence: 99%